Subclinical hypothyroidism of unexplained infertility patients does not affect intrauterine insemination success: A case-control study - Oglak, Suleyman Cemil; Obut, Mehmet (Annals of Medical Research, 2021)
Aim: This study aimed to assess the importance of preconceptional thyroid-stimulating hormone (TSH) values on the achievement of intrauterine insemination (IUI) in unexplained infertile patients.Materials and Methods: This study was conducted retrospectively by evaluating the medical records of euthyroid 192 patients who experienced IUI between January 2017 and December 2018. The study population was classified as serum TSH levels of 0.5-2.49 mIU/L (group A) and 2.5-4.5 mIU/L (group B). Clinical pregnancy, miscarriage and live birth rates of the groups were evaluated. Results: The demographic characteristics, laboratory levels, and cycle characteristics of the study population were similar. There were no statistically significant differences between group A and group B in terms of clinical pregnancy (11.03%, and 8.51%, respectively, p=0.62), miscarriage (3.55%, and 1.13%, respectively, p=0.65), and live birth rates (7.58%, and 6.38%, respectively, p=0.78). Conclusion: Clinical pregnancy, miscarriage, and live birth rates were similar between the two groups. We indicate that subclinical hypothyroidism does not adversely affect the clinical pregnancy, miscarriage, and live birth rates in IUI cycles of euthyroid unexplained infertile couples.
Keywords: Clinical pregnancy; intrauterine insemination; thyroid-stimulating hormone; unexplained infertility